Looking for Ladyhood: Desegregation-Era Black Church Feminine-ism and the Ocular Politics of Respectability in R. C. Hickman’s Photographic Archive - Evans, Jade (Journal of the American Academy of Religion, 2025)
Scholars of African American religious history who access traditional archives to narrate Black women’s religious experiences ought not neglect the pertinent material sources available in the photographic archive. In this article, I consider how vernacular photography found in R. C. Hickman’s photographic archive uncovers important nuances of Black church respectability politics in Dallas, TX from the 1940s to 1960s. Though vernacular photography is a complicated source of historical knowledge, I argue that one of Hickman’s photographs in particular puts what Tamura Lomax calls "feminine-ism" on display. By situating this photo within discourse on religion and racial politics in the desegregation era, this article models how scholars can explore photographic archives to fill gaps in African American women’s religious history. Thus, this article prompts scholars of African American religious history to embrace the photograph as a significant material source and, thereby, become scholarly witnesses of Black women’s religious lives.